Short-term impact of a university based smoke free campaign. Issue 11 (1st November 1999) - Etter, J F; Ronchi, A; Perneger, T
Abstract : STUDY OBJECTIVE: The aim of this study was to evaluate the impact of a smoke free programme implemented at the University of Geneva, Switzerland, in 1996. This programme included a prohibition to smoke in university buildings everywhere except in limited areas, and a smoking cessation counselling service. METHODS: Surveys were conducted before and four months after the programme was implemented, in representative samples of programme participants (n = 833) and university members not exposed to the programme (n = 1023). RESULTS: In retrospective assessments, participants reported being less bothered by environmental tobacco smoke after programme implementation, but no between group difference was detected in prospective assessments. Relationships between smokers and non-smokers improved moderately in the intervention group and remained unchanged in the comparison group (between group p = 0.001). Proportions of smokers who attempted to quit smoking in the past four months increased from 2.0% to 3.8% in the intervention group and remained unchanged at 3.5% in the comparison group (between group difference: p = 0.048). No impact on smoking prevalence (25%) was detected. The programme was appreciated by university members, although some of its modalities were criticised. CONCLUSION: A regulation prohibiting smoking everywhere but in limited areas of university buildings was acceptable and reduced the perception of bother by environmental tobacco smoke. It did not, however, influence smoking habits or attitudes toward smoking.